Xist RNA repeat E is essential for ASH2L recruitment to the inactive X and regulates histone modifications and escape gene expression. - Minghui Yue; Akiyo Ogawa; Norishige Yamada; John Lalith Charles Richard; Artem Barski; Yuya Ogawa (PLoS Genetics, 2017)
Long non-coding RNA Xist plays a crucial role in establishing and maintaining X-chromosome inactivation (XCI) which is a paradigm of long non-coding RNA-mediated gene regulation. Xist has Xist-specific repeat elements A-F which are conserved among eutherian mammals, underscoring their functional importance. Here we report that Xist RNA repeat E, a conserved Xist repeat element in the Xist exon 7, interacts with ASH2L and contributes to maintenance of escape gene expression level on the inactive X-chromosome (Xi) during XCI. The Xist repeat E-deletion mutant female ES cells show the depletion of ASH2L from the Xi upon differentiation. Furthermore, a subset of escape genes exhibits unexpectedly higher expression in the repeat E mutant cells than the cells expressing wildtype Xist during X-inactivation, whereas the silencing of X-linked non-escape genes is not affected. We discuss the implications of these results to understand the role of ASH2L and Xist repeat E for histone modifications and escape gene regulation during random X-chromosome inactivation.